AKREDITASI PENYELENGGARA PERJALANAN IBADAH UMROH (PPIU) SEBAGAI BENTUK KEPATUHAN TERHADAP HUKUM POSITIF DAN PERLINDUNGAN KONSUMEN - Pardiansyah, Dedi; Lulus Setiawan, Wawan (Penerbit Lafadz Jaya, 2025)
Organizing Umrah and Hajj pilgrimage trips is included in the Regular Business category where all operations must be guided by positive law comprehensively, starting from licensing of the organizers to service standards to the congregation as consumers. The implementation of the Umrah pilgrimage is regulated and supervised by the government, in this case by the Ministry of Religion of the Republic of Indonesia (KEMENAG R.I) by providing accreditation for Umrah pilgrimage organizers (PPIU). However, it is necessary to examine the extent to which PPIU accreditation is a form of positive legal compliance and consumer protection. Based on this phenomenon, the author conducted research with the title